2004
DOI: 10.1016/s0006-3495(04)74286-1
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction from a Left Ventricular Wall of Rat Heart

Abstract: We studied x-ray diffraction from the left ventricular wall of an excised, perfused whole heart of a rat using x rays from the third-generation synchrotron radiation facility, SPring-8. With the beam at right angles to the long axis of the left ventricle, well-oriented, strong equatorial reflections were observed from the epicardium surface. The reflections became vertically split arcs when the beam passed through myocardium deeper in the wall, and rings were observed when the beam passed into the inner myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 12 publications
3
38
0
Order By: Relevance
“…The absolute value of diastolic SL reported here (2.09±0.168 µm) is consistent with results from other groups (1.96-2.1 µm for histological 42 and x-ray diffraction studies, 43 respectively). However, it is higher than the value we previously obtained in a similar preparation (1.95 µm) 13 using a conventional 2-photon microscope.…”
Section: Discussionsupporting
confidence: 93%
“…The absolute value of diastolic SL reported here (2.09±0.168 µm) is consistent with results from other groups (1.96-2.1 µm for histological 42 and x-ray diffraction studies, 43 respectively). However, it is higher than the value we previously obtained in a similar preparation (1.95 µm) 13 using a conventional 2-photon microscope.…”
Section: Discussionsupporting
confidence: 93%
“…Such a mechanism can explain the abrupt transitions that we observed in myofilament calcium sensitivity, I 1,1 /I 1,0 intensity ratio, and interfilament spacing at low levels of applied osmotic compression. A difficulty with this view, however, is that it conflicts with recent studies (30,39) that measured myofilament lattice spacing and I 1,1 /I 1,0 intensity ratio in whole hearts. Both studies reported a diastolic (relaxed) I 1,1 /I 1,0 intensity ratio of ϳ0.4, equivalent to the compressed patterns we observed in the skinned fibers, but the reported myofilament lattice spacing was very different between the two studies: ϳ42 nm (30) and ϳ37.5 nm (39).…”
Section: Osmotic Pressure Sensitive Switch For Calcium Sensitivity?mentioning
confidence: 77%
“…By exposing a finely collimated SR X-ray beam (dimensions, 0.2×0.2 mm) to the whole heart, it is now possible to record the diffraction peaks in a myocardial region without averaging over multiple heart beats at a time resolution of 15 to 20 ms. [78][79][80] The time resolution is not limited by the available flux but mainly by radiation damage. Studies of a whole heart started with the isolated rat heart.…”
Section: Current and Past Saxs Studies From Myocytes To The In Situ Hmentioning
confidence: 99%
“…Studies of a whole heart started with the isolated rat heart. 80 Use of a whole heart has the advantage that it is more physiological than an isolated muscle, and because the mass is larger the diffraction intensity is higher. This helps to reduce the radiation damage.…”
Section: Current and Past Saxs Studies From Myocytes To The In Situ Hmentioning
confidence: 99%
See 1 more Smart Citation